Gerakan Cuci Tangan yang Benar dan Edukasi Pencegahan Penyakit Cacingan pada Anak Sekolah Dasar - Nur Fauziah, Ani; Anasarini; Septie Nursita, Triyas; Affrikia Sari, Fila; Nur Qomari’ah, Anisa; Yuliani Nur Fadilah, Rizka; Nailah Latif, Zakhrotun (PADMA, 2024)
Helminthiasis infections are most prevalent in Indonesia, with the highest prevalence in school-aged children aged 3-14 years. If left untreated over a long period of time, children can suffer from malnutrition and even protein energy deficiency. Prevention of worm infections can be achieved through the proper implementation of PHBS in schools, which involves washing hands with soap and running water for 40-60 seconds. Efforts to prevent this disease are correct hand washing movement activities and education on prevention of worms in primary school children carried out from 01 to 12 February 2024 with a total of 54 students using hand washing songs and leaflets on prevention of helminthiasis in primary school children. students gained increased knowledge about the correct hand washing movement and prevention of helminthiasis